EFFECT OF FRICTION STIR PROCESSING (FSP) ON THE MICROSTRUCTURE AND MECHANICAL PROPERTIES OF ADDITIVELY MANUFACTURED TI-6AL-4V - Kyrylakha, S. V. (Systems and Technologies, 2025)
This study investigates the influence of Friction Stir Processing (FSP) on the microstructure and mechanical properties of additively manufactured Ti-6Al-4V alloy. A hybrid technological route, “additive manufacturing + friction stir welding (AM + FSW),” was employed, involving electron beam melting (EBM) for the fabrication of initial samples, followed by FSP to enhance structural integrity. The research focuses on the detailed characterization of weld zones, including the stir zone (SZ), thermo- mechanically affected zone (TMAZ), and heat-affected zone (HAZ). Microstructural analysis was conducted to evaluate grain orientation, β-phase recrystallization, and deformation gradients, while mechanical testing assessed ultimate tensile strength and plasticity. Comparative analysis with conventional FSW of pure titanium highlighted specific features of additively manufactured Ti-6Al-4V, such as the influence of the initial columnar grain structure and intrinsic melting-induced defects on the formation of a fine-grained SZ and the overall mechanical performance of the joints. Results indicate that optimization of FSP parameters, particularly tool rotational speed and traverse rate, critically affects microstructural homogeneity, defect elimination, and enhancement of mechanical properties. The findings demonstrate that the hybrid AM + FSW route can effectively compensate for typical additive manufacturing defects, improving isotropy, tensile strength, and ductility of structural components. This research provides a scientific basis for the further development and optimization of hybrid manufacturing routes, allowing for the prediction and control of mechanical behavior in high-performance Ti-6Al-4V components intended for aerospace and transport applications. The integration of additive manufacturing with friction stir processing represents a promising strategy to produce reliable, high-quality titanium alloy components with enhanced durability and mechanical resilience.